Teamwork in First Year Law Units: Can It Work? - Carver, Tracey; Stickley, Amanda (Journal of University Teaching and Learning Practice, 2012)
There is an abundance of literature on the importance of teamwork in undergraduate degrees; how to teach it, how to assess it and how to manage it. However, there is also much recorded about students’ dislike of teamwork, especially where an early experience is unsatisfactory and builds resistance against such assessment. Accordingly, despite the revolution of embedding skills into undergraduate university courses, this article commences by examining the issues which commonly arise as impediments to implementing teamwork in this environment – both generally, and in the context of the particular discipline of law. It then examines how the teaching and assessment of teamwork was embedded into a first year law unit at the Queensland University of Technology (‘QUT’). Finally, student perceptions of the model implemented are described. These show that, despite the odds, students generally considered that the model had an effective and positive influence upon their learning experience and outcomes.